A model for setting a regulatory framework for the development of suborbital operations in Italy. Issue 3 (September 2017) - Di Antonio, Giovanni; Sandrucci, Marco; Cardi, Alessandro; Santoro, Francesco; Del Bianco, Alberto; Romanelli, Cristoforo
Abstract: This paper describes the model currently under discussion in Italy which has been developing for setting up a regulatory framework for commercial suborbital operations. This model is expected to accommodate in the near-midterm HOTOL (Horizontal Take-Off and Horizontal Landing) suborbital operations within the national aviation system, the national airspace and using existing facilities, taking into account the relevant international regulatory experience in the field. An adequate level of safety for uninvolved people on the ground, in the air, at sea and for critical infrastructures will be primarily sought along with due considerations for the safety of involved people onboard, in line with the state of the art and the technological development of the sector.